Smart Vacuum Cleaner Robot - A.Nalini (International Journal of Engineering and Management Research, 2019)
The development of intelligent vacuum cleaner robots marks a significant turning point in the history of home appliances. The seamless and effective cleaning experience provided by these self-contained, intelligent devices allows homeowners to devote their valuable time to other worthwhile activities. The smart hoover cleaner robot market is expected to revolutionise how we approach cleanliness and convenience in contemporary homes with ongoing improvements and innovations on the horizon.